Antibacterial activity of ginger extracts and its essential oil on some of pathogenic bacteria - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
The antimicrobial activity of ginger extracts ( cold-water, hot-water, ethanolic and essential oil ) against some of pathogenic bacteria ( Escherichia coli , Salmonella sp , Klebsiella sp , Serratia marcescens, Vibrio cholerae , Staphylococcus aureus , Streptococcus sp) was investigated using Disc diffusion method , and the results were compared with the antimicrobial activity of 12 antibiotics on the same bacteria . The results showed that the ginger extracts were more effective on gram-positive bacteria than gram-negative . V. cholerae and S. marcescens,were the most resistant bacteria to the extracts used , while highest inhibition was noticed against Streptococcus sp (28 mm) . The ethanolic extract showed the broadest antibacterial activity ( 11 to 28 mm ) , in comparison with moderate activity of essential oil , it was observed that the cold-water extract was more effective on the bacteria than hot-water extract . Ginger ethanolic extract presented higher diameter of inhibition zone for Streptococcus sp than in Ciprofloxacin , Cefotaxime , Cefalotin , Cephalexin and Cephaloridine , also it was found a similarity between the higher inhibition zones of ethanolic extract of ginger and some antibiotics for S. aureus , E. coli , Salmonella sp and Klebsiella sp . V. cholerae and S. marcescens,also highly resistant to antibiotics . Phytochemical analysis of ethanolic extract of ginger revealed the present of glycosides, terpenoids, flavonids and phenolic compounds